1996
DOI: 10.1128/aac.40.9.2087
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose and steady-state pharmacokinetics of hypericin and pseudohypericin

Abstract: Single-dose and steady-state pharmacokinetics of antivirally acting hypericin (H) and pseudohypericin (PH) were studied in 13 healthy volunteers by administration of St. John's Wort extract LI 160, a plantal antidepressant. Oral administration of 250, 750, and 1,500 micrograms of H and 526, 1,578, and 3,156 micrograms of PH resulted in median peak levels in plasma (Cmax) of 1.3, 7.2, and 16.6 micrograms/liter for H and 3.4, 12.1, and 29.7 micrograms/liter for PH, respectively. The Cmax and the area under the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(84 citation statements)
references
References 21 publications
7
74
0
3
Order By: Relevance
“…Die Substanzen werden rasch resorbiert (maximale Plasmaspiegel nach 2-6 h) und in einer nicht linearen Kinetik eliminiert. Die Halbwertszeiten betragen ungefähr 15 (Hyperforin) bis 30 (Hypericine) Stunden [4,9,25,53,57].…”
Section: Pharmakokinetische Datenunclassified
See 1 more Smart Citation
“…Die Substanzen werden rasch resorbiert (maximale Plasmaspiegel nach 2-6 h) und in einer nicht linearen Kinetik eliminiert. Die Halbwertszeiten betragen ungefähr 15 (Hyperforin) bis 30 (Hypericine) Stunden [4,9,25,53,57].…”
Section: Pharmakokinetische Datenunclassified
“…Im Gegensatz zur fehlenden Photosensibilisierung bei Einnahme von Johanniskrautextrakt kam es in einer Studie, bei der HIV-infizierte Patienten mit reinem Hypericin oral oder intravenös behandelt wurden, bei fast allen Patienten zu schweren phototoxischen Symptomen [19].Verschiedene pharmakokinetische Untersuchungen lassen darauf schließen,dass der phototoxische Schwellenwert von Hypericin durch orale Einnahme antidepressiver Johanniskrautextrakte bei weitem nicht erreicht wird [9,25,47,53].In diesen Studien lagen die maximalen Serumspiegel für Hypericin zwischen 12 und 61 ng/ml (Tabelle 2).…”
Section: Phototoxizitätunclassified
“…pills or drops). Thus, the expected hypericin concentrations in blood are in the range of 1 to 10 ng mL -1 [21,22,23]. In the case of a higher dosage, higher levels of hypericin in blood are likely [24].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies in humans have revealed that clinically relevant dosages of total hypericin (approximately 1 mg/day) reach a maximal plasma concentration in the nanomolar to micromolar range after 4-6 h, and achieve a steady-state after about 4 days (Brockmöller et al 1997;Kerb et al 1996;Staffeldt et al 1994;Upton et al 1997). The absorptive lag-time is roughly twice as long for hypericin (approximately 2 h) versus pseudohypericin (approximately 1 h), and elimination of both compounds is reported to be slow; approximately 25 and 40 h, respectively (Staffeldt et al 1994).…”
Section: Pharmacokineticsmentioning
confidence: 95%